2018
DOI: 10.12973/iji.2018.11459a
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Academic Motivations and University Students’ Attitudes towards Learning

Abstract: The aim of this research is to examine the relationship between university students' attitudes towards learning and their academic motivations. This is a relational survey model study and the population composed of university students studying at a state university. The sample is composed of the university students determined according to stratified sampling method among the related university students. The "Attitude Toward Learning Scale" and "Academic Motivation Scale" were used in the study. According to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 39 publications
2
16
0
5
Order By: Relevance
“…A student who has a positive attitude to learning has a learning outcome which is better compared to a student who has less positive attitude to learning (Bakar et al, 2010). Another study also concluded a positive and significant relationship between learning attitudes and academic motivation, and there was a high and positive correlation between intrinsic, extrinsic motivation and academic motivation (Tasgin & Coskun, 2018). Students with high achievement motivation also have more positive attitude to the exam they will face (Adegboyega, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…A student who has a positive attitude to learning has a learning outcome which is better compared to a student who has less positive attitude to learning (Bakar et al, 2010). Another study also concluded a positive and significant relationship between learning attitudes and academic motivation, and there was a high and positive correlation between intrinsic, extrinsic motivation and academic motivation (Tasgin & Coskun, 2018). Students with high achievement motivation also have more positive attitude to the exam they will face (Adegboyega, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…More recent evidence, however, suggests that extrinsic motivation, in combination with intrinsic motivation may promote deep learning (Mo, 2011). Also, extrinsic motivation may trigger intrinsic motivation and thereby strengthen deep learning (Rassuli, 2012) and lead to better academic performance (Tasgin & Coskun, 2018). This is also supported by recent research in a business studies context, where accounting students with high intrinsic and extrinsic motivation tended to be more engaged in deep learning (Everaert et al, 2017).…”
Section: Motivation and Learning Approachesmentioning
confidence: 83%
“…A partir del análisis de la información recabada en este estudio y de aquello que muchos otros trabajos de investigación han defendido (Chien y Hsieh, 2018;Tasgin y Coskun, 2018), se ha podido constatar que la motivación que presentan estos jóvenes escolarizados en las etapas educativas de Educación Secundaria Obligatoria y Bachillerato, depende más de la metodología de enseñanza-aprendizaje y la actuación pedagógica adoptada por el docente -lo que bien se conoce como el "cómo se enseña"-, que del contenido en sí mismo que en cada materia se aborda -lo que se conoce como el "qué se enseña"-.…”
Section: Conclusiones Y Discusiónunclassified